2022
DOI: 10.1007/s40516-022-00185-3
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Melt Pool and Porosity During Laser Powder Bed Fusion of Ti6Al4V Alloy: Numerical Modelling and Experimental Validation

Abstract: Laser powder bed fusion (L-PBF) is one of the most promising additive manufacturing technologies for metals. In this work, the discrete element method (DEM) was used to reproduce a powder bed of particles distributed in a random way to be as close as possible to reality. Single and multiple scan tracks simulations were performed for Ti6Al4V alloy using a commercial CFD software, FLOW-3D AM®. The output from the numerical simulations was elaborated to obtain shape and size of melt pools, morphology of scan trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…These pores are usually spherical in shape and smaller in size (<100 µm) when compared to the other two kinds of internal defects discussed above [ 225 ]. Gas pores are known to occur during the evolution of the melt pool, when it is largely unstable and gas from the environment gets entrapped [ 226 ]. It should be noted that gas defects are more likely to occur when the density of the Ti6Al4V powder is low before the 3D-printing process starts [ 206 , 227 ].…”
Section: Microstructural Imperfections In Slm-built Ti6al4v Constructsmentioning
confidence: 99%
“…These pores are usually spherical in shape and smaller in size (<100 µm) when compared to the other two kinds of internal defects discussed above [ 225 ]. Gas pores are known to occur during the evolution of the melt pool, when it is largely unstable and gas from the environment gets entrapped [ 226 ]. It should be noted that gas defects are more likely to occur when the density of the Ti6Al4V powder is low before the 3D-printing process starts [ 206 , 227 ].…”
Section: Microstructural Imperfections In Slm-built Ti6al4v Constructsmentioning
confidence: 99%
“…Meanwhile, Lu Wang et al [ 85 ] used a coupled multi-physical field model including heat transfer, liquid flow, metal vaporization, margin effect, and Darcy’s law for numerical simulation, mainly simulating the velocity field and temperature field of the melt pool, etc., while using high-speed X-ray imaging for experimental verification, and found that the uneven distribution of recoil pressure on the surface of the keyhole increases the formation of keyhole pores; in addition, different process parameters also affect the formation of keyholes, while low ambient pressure can reduce or even eliminate the formation of keyhole pores, and the instability of the keyhole leads to the formation process of pores, as shown in Figure 11 . In addition to the numerical simulation analyses of the melt pool by the above scholars, other scholars have also conducted related studies [ 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ], where scholars have mainly focused on the process of keyhole generation, the influence of process parameters and processing atmosphere on the melt pool morphology, and the relationship between the unstable state of the melt pool and part defects. At the same time, a multi-physics field coupling model was established to simulate the process of laser and metal powder interaction in a more realistic way.…”
Section: Mechanism Of Metal Evaporation In the Lpbf Processmentioning
confidence: 99%
“…), or the anisotropy [7] in material properties. Thermomechanical simulation [8,9], and inherent strain approach [10,11] are two types of finite element (FE)-based simulation techniques frequently used for predicting properties of additively manufactured components ranging from melt pool prediction [12][13][14] to final residual stresses [15] and component distortions. Thermomechanical simulation is a more systematic and sequential approach in which the first step thermal analysis (TA) yields a transient temperature field, which is used as the thermal load to drive the subsequent mechanical analysis (MA) step.…”
Section: Introductionmentioning
confidence: 99%